Terampil Membaca Dengan Pengajaran Kelancaran Membaca Gaya Credo - Wati, Rani Mulia; Salim, Herli (Universitas Pendidikan Indonesia Kampus Serang, 2021)
In this study, the researcher tried to explain the application of credo-style fluency teaching to improve reading skills of elementary school students, where they have gone through the prefix reading process so that high-grade students should be able to read fluently with understanding. But in reality, after students are tested using the KBPM standard (Correct Words Per Minute), there are still many students who get scores below their class ability level. Respondents in this study were grade 6 elementary school students. This research uses qualitative methods with case studies. The data in this study were obtained through observations made virtually due to the pandemic, interviews with teachers and the Credo team, and documentary studies to see the implementation plan of learning and student outcomes after teaching. The conclusion of this study is the teaching of Credo style fluency is carried out in three stages, namely pre-test, teaching, and post-test. To be able to carry out Credo style teaching, a preliminary test must be carried out to see the students' abilities. All students who took fluency teaching experienced a significant change as seen from the increased KBPM score during the post-test and the student's ability to answer questions during text discussion. Out of a total of 7 students, 4 students managed to advance one level from their pre-teaching ability. It concluded that Credo style was assumed as effective to elementary school.